Protein degradation - Goldberg, Alfred (Henry Stewart Talks, 2007)
Protein levels in cells are regulated by their rates of synthesis and degradation, Regulatory proteins are rapidly degraded by the ubiquitin-proteasome pathway, Examples include many oncogenes, transcription factors and cyclins which control progress through the cell cycle, NF-kappa B activation in disease depends on degradation of the inhibitor, I-kappa B, Misfolded or mutant proteins are rapidly degraded, Neurodegenerative and protein folding diseases, Two major proteolytic pathways exist in mammalian cells, Many acid hydrolases exist in lysosomes, Endocytosed proteins and those in autophagic vacuoles are degraded in lysosomes, The ubiquitin-proteasome pathway, 3D structure of ubiquitin, Formation of the isopeptide bonds during ubiquitin conjugation to proteins, The ubiquitin-proteasome pathway, Proteasome function is linked to ATP hydrolysis, Proteasomes unfold proteins and translocate them into 20S particles, Three types of peptidase sites, Proposed mechanism of proteasome inhibitors, Therapeutic applications of proteasome inhibitors, Two systems for protein breakdown function in the two pathways for antigen presentation, Changes in proteasome subunits induced by interferon, Steps involved in generating antigenic peptides
Reviewed at 2016/01/19